Reception of Tolerance Verses Across Academic Habitus: PTKI Students and Digital Polarization - Husnul Hamidatul Munauwarah; Rofiqa Zulfa Salsabila; Zira Shafira; Kamila Naim; Ibnu Ahmad Dzakir (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
Inter-sectarian debates on social media have triggered sharp internal polarization among Muslims. While previous Living Qur'an studies overlook institutional academic habitus in verse reception, this research explores how Islamic Studies master's students from five PTKIs; UIN Jakarta, PTIQ Jakarta, UIN Yogyakarta, UIN Banjarmasin, and UNIDA Gontor reproduce tolerance verses responding to digital internal conflicts. Employing a qualitative Living Qur'an approach with sociology of knowledge and habitus analysis, this study involved 22 purposively selected informants. The study reveals three primary findings. First, students' reception of tolerance verses is non-monolithic, spanning six intersecting paradigms that demonstrate the text's flexibility when engaging with readers' distinct habitus. Second, digital responses are polarized between disengagement strategies as academic distinction mechanisms and varied active strategies. Third, students' reception is constructed by an interlocking web of academic habitus, undergraduate background, organizational activism, cross-disciplinary interactions, fragmented reference authority, and digital literacy. This study demonstrates that religious moderation in the digital sphere is profoundly shaped by students' academic habitus, institutional ecosystems, and critical digital literacy.